PHENOMENOLOGY OF SPORT IN CONTEMPORARY SOCIETY (Heritage, 2020)
The very phenomenon of sport is extremely ambiguous. We can deal with it from a physical-motor point of view, but at the same time we can see it as a broader social and humanistic phenomenon. Different definitions and approaches to sport imply the need to introduce a systematic concept that can contribute to a better understanding of the meaning and role of sport, not only in the life of an individual, but also in society as a whole. Modern sport does not refer exclusively to the spheres of individual and private choices but includes a large number of people in its realization and has a wide social and cultural significance. This paper emphasizes that with careful monitoring and analysis from the point of view of social sciences and humanities, sport requires exhaustive analysis, so that it can increasingly achieve its authentic goals and create incentives for comprehensive development, not only of each individual, but also the promotion of society as a whole. This approach to sports reality enables the evaluation of abilities, modeling of lifestyles in response to the new needs of modern man, assessment of the impact on personal and collective behavior, and differentiation of the important from the irrelevant. The current practice of sports development in the world clearly shows that it is impossible to imagine the life of a modern man only from economic aspects. The multidisciplinary approach does not exclude the dominant importance of the economic aspect of sports development in relation to social, cultural, health, medical, environmental… These views point to the necessary involvement of experts of various profiles in research into the development of sport itself, but also confirm the thesis that research and disregard research results from different non-economic positions.
Keywords: sport, the phenomenon of sport, the social-humanistic phenomenon, modern society